The Three Stooges funniest moments - Three Stooges (Comedy team); Film Shows, Inc. (Firm); GoodTimes Entertainment; GoodTimes DVD. (New York, N.Y. : GoodTimes DVD, 2000)
Glimpses of Moe Howard, Larry Fine and Curly Joe DeRita in color which were shot in 1965 as live-action scenes for The New Three Stooges cartoon show.
"Rare glimpses of Moe, Larry and Curly Joe in color."-- Container.
Executive producers, Ken Cayre, Stan Cayre, Joe Cayre ; creative consultant, Ken Cayre.
The Three Stooges.
DVD ; DVD player required ; standard full frame (1.33:1) ; single layer ; dolby digital mono.
Keywords: Three Stooges (Comedy team) -- Drama; Comedy television programs